A Review on Unani and Modern Aspects of Psoriasis (Da’u-us-Sadaf) Treatment - Nasir, Abdul; Fatma, Gazala; Ali, Waris; Ahmad, M. Aftab (Recent Developments in Medicine and Medical Research Vol. 6, 2021)
Psoriasis (Da'u-us-Sadaf) is a common, disfiguring, inflammatory, and chronic autoimmune skin illness that affects people all over the world. Europeans have the highest incidence, while Asians from the East have the lowest. In India, the prevalence of psoriasis in adults ranges from 0.44 percent to 2.8 percent. The name psoriasis derived from the Greek word psora, which means "itch," and iasis, which means "activity, condition." Da'u-us-Sadaf is formed from the Arabic terms "daun" and "Sadaf," which mean "disease" and "oyster shell," respectively. Since ancient times, psoriasis or Da'u-us-Sadaf has not been mentioned in any classic literature. Famous Unani physicians Razi, Majoosi, Ahmad Bin Mohd Tabari, Ibn-e-Zohr, Akbar Arzani, and Azam Khan viewed it in the context of Taqashur-e-Jild and Qashaf-e-Jild because of dryness of the skin and scale formation, which clinically resembles psoriasis (Da'u-us-Sadaf). According to Ali Ibn-e-Abbas Al- Majoosi, Tabiyat expels the Khilt-e-Ghaleez from internal organs to the skin, causing dryness and itching, but the skin is unable to eliminate the Khilt-e-Ghaleez, resulting in the accumulation of sauda in the skin and the production of Taqashur-e-Jild. Unani scholars has emphasized the Usool-e-Ilaj (principle of treatment) ,which includes evacuations of black bile (Istifragh or Tanqiyahe Sauda), use of blood purifier (Tasfeeh-e-Dam), Munzijate Sauda (Melancholic concoctives), Mushilate Sauda (Melancholic purgatives), Tabreed Badan (genesis of ratoobat or fluids in the body), try to restore normal temperament (Tadeele Mizaj), topical application of jali (detergent), murakhi (emollient), murattib and mohallil (anti-inflammatory) advia. In this review we have tried to discuss about Unani and modern aspects of psoriasis (Da’u-us-Sadaf). Objectives: To review the treatment of psoriasis through modern medicine as well as unani medicine. To know about facts of psoriasis.